Detection, treatment, and prevention of carbapenemase-producing Enterobacteriaceae: Recommendations from an International Working Group. (June 2013) - Hara, Gabriel Levy; Gould, Ian; Endimiani, Andrea; Pardo, Pilar Ramón; Daikos, George; Hsueh, Po-Ren; Mehtar, Shaheen; Petrikkos, George; Casellas, José María; Daciuk, Lucía; Paciel, Daniela; Novelli, Andrea; et al.
Abstract : The prevalence of carbapenemase-producing Enterobacteriaceae (CPE) has increased during the past 10 years. Its detection is frequently difficult, because they do not always show a minimum inhibitory concentration (MIC) value for carbapenems in the resistance range. Both broth microdilution and agar dilution methods are more sensitive than disk diffusion method, Etest and automated systems. Studies on antimicrobial treatment are based on a limited number of patients; therefore, the optimal treatment is not well established. Combination therapy with two active drugs appears to be more effective than monotherapy. Combination of a carbapenem with another active agent — preferentially an aminoglycoside or colistin — could lower mortality provided that the MIC is ≤4 mg/l and probably ≤8 mg/l, and is administered in a higher-dose/prolonged-infusion regimen. An aggressive infection control and prevention strategy is recommended, including reinforcement of hand hygiene, using contact precautions and early detection of CPE through use of targeted surveillance.